The Woody Plants and Landscape Values of the Historical Public Garden of in and the Town of Canakkale - Erbesler Ayasligil, Tulay (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2019)
Urban open and green areas, especially where old mature odunsu reached the age groves and parks, landscape architecture holds an important place in the studies to be made regarding. Important regional and local landscape character at the scale of the structure, reflecting the region's ecology is compatible with the protection of areas of resistant vegetation is important in terms of sustainability. In the historical process of this kind survived until the present day landscape of the area of the woody vegetation species which occur in the uncovering of the survey area habitat conditions, and will contribute to the science of determining the performance of these species. For this purpose, the most important of The Historical Public Garden the town of Canakkale open and green woody vegetation from the area of the region and the historical development of the city, the region and the current ecological characteristics of vegetation has been identified. 2016-2017 the year of observation and the identification perennial woody plant species existing in the four seasons, height, diameter, crown widths, development, and health conditions, good growing harmonious to the landscape and vegetation of the region have been revealed. A total of 1,200 plants have been identified as trees and shrubs in the historic gardens. Existing vegetation, deciduous broad-leaved trees, the majority of (576). Of them, 57.1% tall trees (329), 25.2% in trees of short stature (145) and 17.7% medium-stature trees (102) comprises. Historic garden within a well developed, tall trees, there are a total of 28 units: Acer negundo, Gleditsia triacanthos, Maclura pomifera, Platanus orientalis, Ulmus minor, Populus x canadensis, Populus x canescens, Populus tremula, Corpus sanguinea, Myrtus communis, Phillyrea latifolia, Cedrus libani, Cupressus sempervirens, Pinus brutia. For the purpose of special historic public garden protection and improvement proposals have been introduced.
Keywords: canakkale; public garden; English garden; Historical Public Garden; Architecture